IL-24 producing regulatory T and B lymphocytes in endometriosis - Kedzierska, Anna Ewa; Lorek, Daria; Slawek, Anna; Karmowski, Mikolaj; Kalota, Aleksandra; Pajak, Jaroslaw; Chrobak, Agnieszka; Grzymajlo, Krzysztof; Chelmonska-Soyta, Anna (Frontiers in Immunology, 2025)
ProblemUnbalanced production of pro- and anti-inflammatory cytokines by immune cells is a hallmark of endometriosis. IL-24, a member of the IL-10 family, is a pleiotropic cytokine produced by both non-immune cells like astrocytes, keratinocytes, pancreatic myofibroblasts, and endothelial cells and immune cells such as monocytes, macrophages, dendritic cells, NK cells, T cells (including Th2 and Th17), and B cells. However, its expression in regulatory T (Tregs) and B lymphocytes (Bregs) has not been explored. In this study, we determined the expression of IL-24 in Tregs and selected Breg subpopulations in women with endometriosis compared with healthy women.MethodsPercentages of Tregs, B10 cells, immature B cells, and plasmablasts that produce IL-24 were measured in the peripheral blood of women with endometriosis (n=24) and healthy women (n=24) using flow cytometry.ResultsWe observed an increased percentage of IL-24–producing Tregs in the total pool of women with endometriosis and in women with stages III and IV of endometriosis compared to controls. Within the Breg subpopulations, the percentages of IL-24–producing plasmablasts were higher in the overall endometriosis cohort as well as in women with stage IV endometriosis compared with healthy women. In contrast, the percentages of IL-24–producing immature B cells were lower in the endometriosis group than that in the control group.ConclusionsWe have shown, for the first time, that Tregs and Bregs secrete IL-24 and that their percentages are altered in endometriosis. The significance of this cytokine secretion by regulatory cells is unclear, but we speculated that IL-24 may enhance the improper immunosuppressive activity of Tregs and plasmablasts in endometriosis, which enables the implantation and growth of endometrial lesions outside the uterus.